2009
DOI: 10.2527/jas.2008-0912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slow-release urea on ruminal digesta characteristics and growth performance in beef steers

Abstract: Two experiments were conducted to evaluate the effects of slow-release urea (SRU) versus feed-grade urea on ruminal metabolite characteristics in steers and DMI, gain, and G:F in growing beef steers. Experiment 1 used 12 ruminally cannulated steers (529 +/- 16 kg of BW) to monitor the behavior of SRU in the ruminal environment. Compared with feed-grade urea, SRU decreased ruminal ammonia concentration (P = 0.02) and tended to increase ruminal urease activity (P = 0.06) without affecting ruminal VFA molar propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 33 publications
8
30
1
5
Order By: Relevance
“…Differences in pH were observed between Treatments 1 and 2 at 06:00 and between Treatment 1 and Treatments 2, 3 and 5 at 21:00 (P <0.05) (Figure 2). Taylor-Edwards et al (2009b) found similar results in terms of pH between urea and SRU treatments. In contrast, Wahrmund et al (2007), reported that rumen pH tended to be affected by urea source, where Optigen® II tended to have a lower pH than the control and urea treatments.…”
Section: Tablesupporting
confidence: 73%
See 4 more Smart Citations
“…Differences in pH were observed between Treatments 1 and 2 at 06:00 and between Treatment 1 and Treatments 2, 3 and 5 at 21:00 (P <0.05) (Figure 2). Taylor-Edwards et al (2009b) found similar results in terms of pH between urea and SRU treatments. In contrast, Wahrmund et al (2007), reported that rumen pH tended to be affected by urea source, where Optigen® II tended to have a lower pH than the control and urea treatments.…”
Section: Tablesupporting
confidence: 73%
“…The observed low N retention for Treatment 5 could be related to high N excretion, low apparent N digestibility and the low N intake. In contrast with the findings of this study, Taylor-Edwards et al (2009b) found higher faecal N for slow-release urea (SRU) compared with urea. These authors suggested that these findings could be possible only if some of the SRU passed through the digestive tract without being hydrolysed in the rumen.…”
Section: Resultscontrasting
confidence: 55%
See 3 more Smart Citations